The fatal impact : an account of the invasion of the South Pacific, 1767-1840 - Moorehead, Alan, 1910- (Mutual Publishing paperback series, 1966)
"The impact that proves so fatal is that of the white man and his civilization upon the natives of Tahiti and Australia, and upon the animal life of the Antarctic. Captain James Cook and Joseph Banks. . . are the central figures in the book."